Facile synthesis of TiO2/CNC nanocomposites for enhanced Cr(VI) photoreduction: Synergistic roles of cellulose nanocrystals. (1st April 2020) - Li, Yanxiang; Zhang, Jinju; Zhan, Chengbo; Kong, Fangong; Li, Wangliang; Yang, Chuanfang; Hsiao, Benjamin S.
Highlights: Uniform TiO2 nanocrystals grew on the CNC scaffold by a simple hydrolysis method. Direct use of TiO2 /CNC nanocomposites for Cr(VI) photoreduction without the need to remove CNC. TiO2 /CNC nanocomposites showed enhanced photoreduction of Cr(VI) under visible light. CNC played essential roles in nanoscale TiO2 formation and Cr(VI) photoreduction. Abstract: In this study, TiO2 nanocrystals were synthesized in the scaffold of cellulose nanocrystal (CNC) using in situ hydrolysis, where the morphology and size of TiO2 was controlled by CNC's functional groups and surface charge. The resulting TiO2 /CNC nanocomposites showed a superior photocatalytic activity for Cr(VI) reduction under visible light (λ > 420 nm) due to the combined effects of small TiO2 size and ligand-to-metal charge transfer (LMCT) complex between CNC and TiO2 . It was found that the charge-enriched CNC not only acted as a template to direct the crystal growth of TiO2, but also played essential roles on light harvesting and charge transfer thereby promoting the photoreduction of Cr(VI). The demonstrated system represents a unique pathway to develop a lower cost and efficient purification material for remediation of Cr(VI).